Grammar Tips Integrated with Telegram Bot: Strategies to Facilitate Learning English Grammar - Rajistha I Gusti Ngurah Adi; Claria Dewa Ayu Kadek (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
The development of technology is very useful to support students in learning linguistics. This study aims to explain the design and ground in multimodal communication to facilitate students in learning English grammar. This research is a field research located in the English Literature Study Program, Faculty of Letters, at Universitas Warmadewa, which applies qualitative methods. This study employs the theory of multimodal communication. Databases related to grammar tips and evaluations were added and presented with appropriate design through ELIA. The data were taken from the communication logs, and the learn and practice dashboard. Based on the analysis, the design includes three important parts, namely genre, mode, and discourse. The focus of the design is the mode chosen to deliver information (ground). The mode is presented in the form of text such as grammar materials and MCQs. However, the visual mode is presented in the form of graphs and charts that show the progress of students learning grammar materials.